Fractional powers of vector operators and fractional Fourier's law in a Hilbert space. (19th June 2018) - Colombo, Fabrizio; Gantner, Jonathan
Abstract: In this paper we give a concrete application of the spectral theory based on the notion of S -spectrum to fractional diffusion process. Precisely, we consider the Fourier law for the propagation of the heat in non homogeneous materials, that is the heat flow is given by the vector operator: where, are orthogonal unit vectors in, a, b, c are given real valued functions that depend on the space variables, and possibly also on time. Using the -version of the S -functional calculus we have recently defined fractional powers of quaternionic operators, which contain, as a particular case, the vector operator T . Hence, we can define the non-local version, for, of the Fourier law defined by T . We will see in this paper how we have to interpret, when we introduce our new approach called: 'The S -spectrum approach to fractional diffusion processes'. This new method allows us to enlarge the class of fractional diffusion and fractional evolution problems that can be defined and studied using our spectral theory based on the S -spectrum for vector operators. This paper is devoted to researchers working in fractional diffusion and fractional evolution problems, partial differential equations and non commutative operator theory. Our theory applies not only to the heat diffusion process but also to Fick's law and more in general it allows to compute the fractional powers of vector operators that arise in different fields of science and technology.